Consensus: soy isoflavones as a first-line approach to the treatment of menopausal vasomotor complaints. (2nd June 2016) - Schmidt, Mathias; Arjomand-Wölkart, Karin; Birkhäuser, Martin H.; Genazzani, Andrea R.; Gruber, Doris M.; Huber, J.; Kölbl, Heinz; Kreft, Samo; Leodolter, Sepp; Linsberger, Doris; Metka, Markus; Simoncini, Tommaso; et al.
Abstract: The association between an increased uptake of isoflavones and a reduced frequency of menopausal hot flushes was first described in 1992, based on a lower incidence of hot flushes in countries with a high consumption of soy. Since then, numerous clinical trials with various sources of isoflavones including soy and red clover have been presented, with practically all of the studies with adequate design delivering an outcome in favour of isoflavone supplementation. An in-depth risk assessment (EFSA 2015) concludes that the amply available human data does not indicate any suspected harmful effects from a potential interaction of isoflavones with hormone-sensitive tissues in the mammary gland, the uterus and the thyroid gland. Safety was ascertained with long-term intake of up to 150 mg isoflavones per day ingested for the duration of at least 3 years. Moreover, high isoflavone intake was found to have preventive effects with respect to breast cancer. Clinical findings indicate potential benefits of isoflavone exposure even during breast cancer treatment with tamoxifen or anastrozole.